Finite Element Analysis of Vacuum Preloading Effect on Lateral Deformation: A Case Study of Road Embankment - Lim, Aswin; Widjaja, Hasky; Erdian, Andreas (Applied Research on Civil Engineering and Environment (ARCEE), 2024)
Soft soil layers are commonly found in Indonesia, which can bring problems in geotechnical engineering. These conditions can be improved by using physical and/or mechanical properties conditions. Physical and mechanical properties conditions can be changed by preloading method. Preloading method can be applied together with the vacuum pressure. The combination of both methods can consolidate soil layer more rapidly. The method was applied to a project road in Jakarta. In this project, vacuum pressure can give more pressure or suction on the soil layer. On this research, lateral movement occurred were predicted by some effects from the vacuum consolidation. The software program from PLAXIS 2D was used to analyze the lateral movement subjected the water suction. According to the results, vacuum preloading should be performed safely with the distance of more or less 22 meters and the usage of vacuum method will accelerate consolidation.